Cendawan Endofit yang Potensial Meningkatkan Ketahanan Cabai Merah terhadap Penyakit Layu Bakteri - Ana Feronika Cindra Irawati; Yudi Sastro; Sulastri Sulastri; Maggy Tenawidjaja Suhartono; Kikin Hamzah Mutaqin; Widodo Widodo (Jurnal Fitopatologi Indonesia, 2016)
Ralstonia solanacearum has been known to cause bacterial wilt disease on chili pepper.  Despite many reports on the potential use of endophytic fungi to induce plant resistance, its utilization to suppress bacterial wilt disease of chili has not been widely reported.  The aims of this research was to screen potential endophytic fungi that may increase chili resistance against bacterial wilt disease.  Selection of endophytic fungi was done using in vivo and antibiosis test. Strains of fungi were considered the most potent in suppressing the development of bacterial wilt in chilli were identified. Ten out of 62 isolates of endophytic fungi gave the highest suppression on chilli’s bacterial wilt disease.  Most strains of endophytic fungi were able to suppress the development of bacterial wilt disease, but not always positively correlated to the vegetative and generative growth of chilli. Based on the level of disease intensity and the growth of plants were obtained three strains of endophytic fungi that considered potentially suppress the incidence of bacterial wilt disease.  The three isolates was identified as Fusarium solani f.sp. phaseoli (AC-2.13 and AC-4.4) and Trichoderma asperellum (AC-3.18) using morphology and molecular characters. Although all three selected isolates were able to suppress bacterial wilt disease in this study, but application of F. solani f.sp. phaseoli should be considered in practical use since it is generally known as the causal agent of root rot disease of beans